Multicomponent Mechanical Characterization of Atherosclerotic Human Coronary Arteries: An Experimental and Computational Hybrid Approach - Guvenir Torun, Su; Torun, Hakki M.; Hansen, Hendrik H. G.; Gandini, Giulia; Berselli, Irene; Codazzi, Veronica; de Korte, Chris L.; van der Steen, Antonius F. W.; Migliavacca, Francesco; Chiastra, Claudio; Akyildiz, Ali C. (Frontiers in Physiology, 2021)
Atherosclerotic plaque rupture in coronary arteries, an important trigger of myocardial infarction, is shown to correlate with high levels of pressure-induced mechanical stresses in plaques. Finite element analyses are commonly used for plaque stress assessment. However, the required information of heterogenous material properties of atherosclerotic coronaries remains to be scarce. In this work, we characterized the component-wise mechanical properties of atherosclerotic human coronary arteries. To achieve this, we performed ex-vivo inflation tests on post-mortem human coronary arteries, and developed an inverse finite element modeling pipeline, which combined high frequency ultrasound deformation measurements, a high-field magnetic resonance-based artery composition characterization, and a machine learning based Bayesian optimization with uniqueness assessment. By using the developed pipeline, ten cross-sections from five atherosclerotic human coronary arteries were analyzed and the Yeoh material model constants of the fibrous intima and arterial wall components were determined. This work outlines the developed pipeline and provides the knowledge of nonlinear, multicomponent mechanical properties of atherosclerotic human coronary arteries.